Realization of ultrashallow junctions by plasma immersion ion implantation and laser annealing - Vervisch, V.; Etienne, H.; Torregrosa, F.; Roux, L.; Ottaviani, L.; Pasquinelli, M.; Sarnet, T.; Delaporte, P. (Journal of Vacuum Science & Technology B Microelectronics and Nanometer Structures, 2008)
To achieve the requirements of the 45 nm ITRS technology node and beyond, beamline implantation has reached its limit in terms of low energies. Plasma immersion ion implantation (PIII) is thus an alternative doping technique for the formation of ultrashallow junctions for source/drain extension in silicon devices. In this study, the authors present some results obtained on the PIII prototype called PULSION® designed by the IBS French company. In previous works [F. Torregrosa et al. , Proceedings of the 14th International Conference on Ion Implant Technology, 2004 (unpublished); Proceedings of the 16th International Conference on Ion Implant Technology, 2006 (unpublished), p. 6 ], it has been shown that this machine offers the possibility to reach ultralow energy implantations and then to obtain implantation depths of only a few nanometers. One of the main issues is then to highly activate these junctions with a limited diffusion of dopants. Wafers have been implanted by PULSION® with acceleration voltages from 1 to 2 kV at saturation dose, with or without preamorphization implantation (PAI). Then, they have been annealed by a XeCl excimer laser with a wavelength of 193 nm , with energy densities from 275 to 600 mJ ∕ cm 2 and several shots. Electrical and physicochemical characterizations such as secondary-ion-mass spectrometry, four-point probe, and optical noncontact measurements were then performed. In this article, the authors investigate the effects of PAI, implantation parameters, and laser fluence on the junction specifications (depth, sheet resistance, and leakage current).